2008
DOI: 10.1038/ng.230
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a remote Shh forebrain enhancer by the Six3 homeoprotein

Abstract: The secreted morphogen, Sonic hedgehog (Shh) is a significant determinant of brain size and craniofacial morphology1-4. In humans, SHH haploinsufficiency results in holoprosencephaly (HPE)5, a defect in anterior midline formation. Despite the importance of maintaining SHH transcript levels above a critical threshold, we know little about the upstream regulators of SHH expression in the forebrain. Here we describe a combination of genetic and biochemical experiments to uncover a critical pair of cis and trans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
164
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 34 publications
5
164
3
Order By: Relevance
“…Six3 directly regulates Shh expression in the RDVM Jeong et al, 2008). As the amount of functional Six3 decreases in Six3 +/-and Six3 +/ki embryos, it fails to activate Shh expression in the ventral forebrain and subsequently leads to HPElike phenotypes.…”
Section: Elevated Shh Signaling Rescues Semilobar Hpe Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Six3 directly regulates Shh expression in the RDVM Jeong et al, 2008). As the amount of functional Six3 decreases in Six3 +/-and Six3 +/ki embryos, it fails to activate Shh expression in the ventral forebrain and subsequently leads to HPElike phenotypes.…”
Section: Elevated Shh Signaling Rescues Semilobar Hpe Phenotypesmentioning
confidence: 99%
“…We previously showed that Six3 directly activates the expression of Shh in the rostral diencephalon ventral midline (RDVM) of mice Jeong et al, 2008). In turn, Shh maintains the expression of Six3 in the RDVM.…”
Section: Introductionmentioning
confidence: 99%
“…Both genes act as transcriptional repressors by interacting with members of the Groucho family of transcriptional co-repressors Marco-Ferreres et al, 2009) but there is also evidence for their role as transcriptional activators (Jeong et al, 2008;Liu et al, 2006;Reichman et al, 2010). In most vertebrate species, both genes are strongly expressed starting at the gastrula stages in the anterior neural plate, where they are required for early forebrain specification.…”
Section: Introductionmentioning
confidence: 99%
“…Hh function results in transcriptional activation of several targets, many of which encode transcription factors (TFs). The homeobox TF gene six3 is transcriptionally activated by Hh signaling and directly activates shh transcription Jeong et al, 2008). six3 function is essential for correct development of all forebrain derivatives, as mice and human with compromised six3 or shh function develop with a profound forebrain defect termed holoprosencephaly (HPE) (Krauss, 2007).…”
Section: Introductionmentioning
confidence: 99%